Doğal ya da yardımcı üreme teknikleri ile gebe kalan kadınların trimesterlere göre psikososyal sağlıkları - Keskin, Gülfidan (My University, 2014)
Bu çalışma doğal ya da yardımcı üreme teknikleri (YÜT) ile gebe kalan kadınların trimesterlere göre psikososyal sağlıklarını değerlendirmek amacıyla tanımlayıcı, gruplar arası karşılaştırmalı olarak planlanmış ve prospektif olarak yürütülmüştür. Araştırma, Nisan 2012 - Haziran 2013 tarihleri arasında T.C. Sağlık Bakanlığı Kamu Hastaneler Kurumu Zeynep Kamil Kadın ve Çocuk Hastalıkları Eğitim ve Araştırma Hastanesi gebe izlem polikliniğinde 359 gebe ile yapılmıştır. Gebeler 3 grup altında toplanmış, doğal yolla gebe kalan primigravidalar 1. Grubu (n=177, %49.3), multigravidalar 2. Grubu (n=60, %16.7) ve YÜT ile gebe kalanlar da 3. Grubu (n=122, %34) oluşturmuştur. Veriler soru formları ve Gebelikte Psikososyal Sağlığı Değerlendirme Ölçeği (GPSDÖ) ile gebelikte her üç trimesterin son haftasında ve doğumdan 8 hafta sonra olmak üzere dört aşamada toplanmıştır. Tüm gruplardaki gebelerin öğrenimlerinin ortaokul ve lise düzeyinde yoğunluk kazandığı, yaş dışında diğer sosyo-demografik özellikler açısından gruplar arasında anlamlı fark olmadığı belirlenmiştir (p>0.05). Gebelerin gebelikleri süresince psikososyal sağlıklarının iyi/ çok iyi düzeyde olduğu bulunmuştur. YÜT ile gebe kalanlarda tüm trimesterlerde GPSDÖ Kaygı ve strese ait özellikler ile 1. ve 3. Trimesterde Psikososyal destek gereksinimine ait özellikler alt boyut puan ortalamalarının, multigravidalarda ise her üç trimesterde GPSDÖ diğer alt boyutları ve total puan ortalamalarının anlamlı düzeyde daha düşük olduğu saptanmıştır. Sonuçlarımıza göre; çalışma kapsamına alınan gebelerin genel psikososyal sağlıklarının iyi düzeyde olduğu, ancak 2. ve 3. Trimesterde psikososyal sağlıklarında olumsuz yönde etkilenmeler olduğu ve bu etkilenmenin özellikle doğal yolla gebe kalan multigravidalarda ve YÜT ile gebe kalanlarda belirginleştiği söylenebilir. Gebelik, Yardımcı üreme teknikleri ile Gebelik, Trimester, Gebelikte Psikososyal Sağlık

THE PSYCHOSOCIAL HEALTH OF WOMEN PREGNANT THROUGH NATURAL FERTILITY OR ASSISTED REPRODUCTIVE TECHNOLOGIES, BY TRIMESTER This descriptive study was planned as prospective research with intergroup comparisons for the purpose of evaluating, according to trimester, the psychosocial health of women pregnant through natural fertility or Assisted Reproductive Technologies (ARTs). The study was conducted with 359 pregnant women in T. C. Ministry of Health, Public Hospitals Authority Zeynep Kamil Women and Children Diseases Education and Research Hospital's pregnancy monitoring clinic between April 2012 - June 2013. The women were studied in 3 groups, the first and second groups being pregnant through natural fertility as primigravidae (n=177, 49.3%) and multigravidae (n=60, 16.7%), and the third group consisting of women pregnant through ARTs (N=122, 34%). Data were collected with questionnaires and a Psychosocial Health in Pregnancy Scale (PHPS) in 4 stages; at the end of each trimesters of pregnancy and at 8 weeks after delivery. It was determined that the women in all three groups were mostly middle school and high school graduates, and that outside of their ages, there were no statistically significant differences between the groups in terms of their other sociodemographic characteristics (p>0.05). The psychosocial health of the women was found to be good/ very good during the course of their pregnancies. It was observed that the mean scores of the women who had become pregnant through ARTs were lower in the PHPS sub-scale of Attributes of anxiety and stress in all trimesters and in the sub-scale of Attributes of need for Psychosocial Support in the first and third trimesters, whereas in multigravidae, the mean scores on all of the other sub-scales on the PHPS as well as total scores were significantly lower in all three trimesters. According to our results, the psychosocial health of the pregnant women included in the scope of the study was at a sound level, they began to feel negative changes in their psychosocial health in the second and third trimesters, and changes in psychosocial health during pregnancy were more pronounced in multigravidae who became pregnant through natural fertility and in women who became pregnant through ARTs. Pregnancy, Pregnancy through Assisted Reproductive Technologies, Trimester, Psychosocial Health in Pregnancy
Keywords: Gebelik; Kadın Hastalıkları ve Doğum; Psikoloji_Gebelik_Hamilelik; Yardımcı Üreme